2019
DOI: 10.3390/nano9030406
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Oxygen Vacancies and Ni Species on Tuning Selectivity of Ni/ZrO2 Catalyst for Hydrogenation of Maleic Anhydride into Succinic Anhydride and γ-Butyrolacetone

Abstract: ZrO2 nanoparticles, ZrO2 (P) and ZrO2 (H), with different tetragonal phase contents, were prepared. ZrO2 (P) possessed higher tetragonal phase content than ZrO2 (H). Ni/ZrO2 catalysts (10% (w/w)), using ZrO2 (P) and ZrO2 (H) as supports, were prepared using an impregnation method, and were characterized using XRD, Raman, H2-TPR, XPS, and H2-TPD techniques. Their catalytic performance in maleic anhydride hydrogenation was tested. The Ni/ZrO2 (P) catalyst exhibited stronger metal-support interactions than the Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 55 publications
5
21
0
Order By: Relevance
“…The stronger interaction further resulted in the decrease of the oxygen vacancies concentration on surface of ZrO2-based supported nickel catalysts, which probably because a small amount of nickel species entered into oxygen vacancies. This result is consistent with our previous study [17], in that the strong interaction between nickel species and ZrO2 support would lead to a small amount of nickel species entering into the tetragonal ZrO2 lattice, and in HRTEM it had been clearly seen that the lattice spacing of the tetragonal ZrO2 increased from 0.29 nm to 0.30 nm, thereby leading to a significant decrease of the surface oxygen vacancies concentration. Based on the above results, it can be concluded that the introduction of Sc 3+ into ZrO2 changes the surface structure of ZrO2-based supports.…”
Section: Xps Characterizationsupporting
confidence: 93%
See 3 more Smart Citations
“…The stronger interaction further resulted in the decrease of the oxygen vacancies concentration on surface of ZrO2-based supported nickel catalysts, which probably because a small amount of nickel species entered into oxygen vacancies. This result is consistent with our previous study [17], in that the strong interaction between nickel species and ZrO2 support would lead to a small amount of nickel species entering into the tetragonal ZrO2 lattice, and in HRTEM it had been clearly seen that the lattice spacing of the tetragonal ZrO2 increased from 0.29 nm to 0.30 nm, thereby leading to a significant decrease of the surface oxygen vacancies concentration. Based on the above results, it can be concluded that the introduction of Sc 3+ into ZrO2 changes the surface structure of ZrO2-based supports.…”
Section: Xps Characterizationsupporting
confidence: 93%
“…In our aforementioned earlier article [17], the Raman, H2-TPR, and XPS characterization results hinted that there was a relationship between the electronic properties of surface oxygen vacancies on the Ni/ZrO2 catalysts and the surface structure of the ZrO2 supports. However, due to a comparison of only two ZrO2-supported nickel catalysts in the previous article, it was difficult for us to reach an MA is a five-membered ring molecule structure, with C=C, C=O, and C-O-C functional groups.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Zhao et al [21] produced ZrO 2 nanoparticles, ZrO 2 (P) and ZrO 2 (H), with different tetragonal phase content (higher in the former), which was used as support for the preparation of 10 wt % Ni/ZrO 2 catalysts via impregnation. The catalysts were characterized by means of XRD, Raman, H 2 -TPR, XPS, and H 2 -TPD techniques, and their catalytic performance was evaluated under the hydrogenation of maleic anhydride toward succinic anhydride and γ-butyrolacetone.…”
Section: (I) Nanomaterials For Chemicals/organics Synthesis and Biotrmentioning
confidence: 99%